THESIS TITLE: IDENTIFYING STRUCTURAL ELEMENTS IN A TEXT FOR A SPECIFIC PURPOSE - Shamsuddinova Ruqiyaxon; Abduraxmonov Toʻraxon (TADQIQOTLAR, 2025)
Introduction:  When  reading  or  writing  for  a  specific  purpose—such  as academic study, business, or medical communication—it is essential to identify the structural  elements  of  a  text.  These  elements  help  the  reader  understand  the organization,  purpose,  and  key  information  within  the  text.  Recognizing  these structures improves both comprehension and effective communication.